2019
DOI: 10.2147/cmar.s201943
|View full text |Cite|
|
Sign up to set email alerts
|

<p>c-MYC expression in T (III/IV) stage oral squamous cell carcinoma (OSCC) patients</p>

Abstract: Purpose: c-MYC has been noted in many tumor types, but its functional significance and clinical utility in oral squamous cell carcinoma (OSCC) are not well known. Here we studied the expression of c-MYC in correlation to clinical outcome in patients with oral squamous cell carcinoma. Methods: The current study, using immunohistochemical staining, first examined c-MYC expression in OSCC patients and further correlated its expression with clinicopathological parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…In addition, younger OSCC patients (less than 60 years old) with high TIME scores showed better survival rates, and OSCC stage III/IV patients also exhibited the same results. Previous studies have shown that male patients do not appear to benefit from immunotherapy compared with female patients (Lin et al, 2019;. However, our study revealed that male patients with high TIME scores had remarkably higher survival rates than female patients.…”
Section: Discussioncontrasting
confidence: 67%
“…In addition, younger OSCC patients (less than 60 years old) with high TIME scores showed better survival rates, and OSCC stage III/IV patients also exhibited the same results. Previous studies have shown that male patients do not appear to benefit from immunotherapy compared with female patients (Lin et al, 2019;. However, our study revealed that male patients with high TIME scores had remarkably higher survival rates than female patients.…”
Section: Discussioncontrasting
confidence: 67%
“…The overexpression of the MYC gene has also been noted in most patients with oral cancer. For patients with T3 or T4 oral cancer, MYC gene expression is related to the likelihood of survival and can serve as a key biomarker for treatment [37].…”
Section: Discussionmentioning
confidence: 99%
“…Myc, a multifunctional transcription factor, regulates many genes involved in multiple biological processes such as cell growth, proliferation and apoptosis. Moreover, it promotes invasion events by activating MEK–ERK pathways [ 6 , 7 , 8 ]. It is well-known that c-Myc is expressed in many different types of cancer, including HNSCCs, in which c-Myc overexpression is responsible for poor tumor prognosis as well as the self-renewal of tumor stem cells [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%